(untitled) (Czech Journal of International Relations, 1966)
The UN General Assembly has concerned itself since 1962 with the codification and progressive development of the principles of international law relating to friendly relations and co-operation among states in accordance with the UN Charter. The XXth General Assembly adopted - on the initiative of socialist and non-aligned countries - resolution 2103/XX which for the first time expressly assumed and interpreted the viewpoints held by the delegation of the Czechoslovak Socialist Republic ever since the question came up. To start with, the General Assembly declared that the task of the UN in this sphere lied not only in mere study of principles but un their codification and progressive development.